Intracranial tuberculoma mimicking metastasis from renal tumor - Özveren, Faik; Çetin, Hasan; Güner, Alev; Kandemir, Baran (My University, 1997)
A 63-year-old female presented with intracranial tuberculoma manifesting as severe headache. Systemic examination found a mass in the left kidney. The histological diagnosis was tuberculoma after kidney biopsy. Cranial computed tomography found two lesions, in the right frontal and occipital lobes. The intracranial lesions were considered to be tuberculomas. Tuberculosis chemotherapy was continued for 15 months. Her neurological deficit was resolved. Cranial computed tomography showed the lesion in the frontal lobe had disappeared and the lesion in the occipital lobe was reduced in size.
Keywords: Computed tomography; Intracranial tuberculoma; Tuberculosis